A Deep Learning-Based Facial Acne Classification System - Quattrini A; Boër C; Leidi T; Paydar R (Dove Medical Press, 2022)
Andrea Quattrini,1 Claudio Boër,1 Tiziano Leidi,1 Rick Paydar2 1Department of Innovative Technologies, Institute of Information Technologies and Networking (SUPSI), Lugano, Switzerland; 2CHOLLEY SA, Pambio-Noranco, SwitzerlandCorrespondence: Andrea Quattrini, Department of Innovative Technologies, Institute of Information Technologies and Networking (SUPSI), Polo Universitario Lugano - Campus Est, Via La Santa 1, Lugano, CH-6962, Switzerland, Tel +41765397810, Email andrea.quattrini@supsi.chIntroduction: Acne is one of the most common pathologies and affects people of all ages, genders, and ethnicities. The assessment of the type and severity status of a patient with acne should be done by a dermatologist, but the ever-increasing waiting time for an examination makes the therapy not accessible as quickly and consequently less effective. This work, born from the collaboration with CHOLLEY, a Swiss company with decades of experience in the research and production of skin care products, with the aim of developing a deep learning system that, using images produced with a mobile device, could make assessments and be as effective as a dermatologist.Methods: There are two main challenges within this task. The first is to have enough data to train a neural model. Unlike other works in the literature, it was decided not to collect a proprietary dataset, but rather to exploit the enormity of public data available in the world of face analysis. Part of Flickr-Faces-HQ (FFHQ) was re-annotated by a CHOLLEY dermatologist, producing a dataset that is sufficiently large, but still very extendable. The second challenge was to simultaneously use high-resolution images to provide the neural network with the best data quality, but at the same time to ensure that the network learned the task correctly. To prevent the network from searching for recognition patterns in some uninteresting regions of the image, a semantic segmentation model was trained to distinguish, what is a skin region possibly affected by acne and what is background and can be discarded.Results: Filtering the re-annotated dataset through the semantic segmentation model, the trained classification model achieved a final average f1 score of 60.84% in distinguishing between acne affected and unaffected faces, result that, if compared to other techniques proposed in the literature, can be considered as state-of-the-art.Keywords: semantic segmentation, image classification, acne detection, dermatologists, computer vision